2018
DOI: 10.1183/23120541.00009-2018
|View full text |Cite
|
Sign up to set email alerts
|

Advance care planning in severe COPD: it is time to engage with the future

Abstract: Severe chronic obstructive pulmonary disease (COPD) is a progressive and debilitating illness characterised by relentless loss of function, intensifying dyspnoea and frequent exacerbations. COPD patients are evidently at increased risk of depression, frailty and death [1, 2]. Predicting individual short-term prognosis and course of events is difficult if not impossible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
2
0
2
Order By: Relevance
“…Survivors of acute NIV should therefore have future treatment plans discussed and documented, including advance-care planning and patient preferences regarding emergency care decisions in the likely event of future clinical deterioration. Despite international consensus regarding the importance of advance-care planning in patients with severe COPD, barriers to this process persist [31]. A qualitative study by Smith et al [32] demonstrated that although many survivors of acute NIV have contemplated their mortality and preferences regarding future treatment and resuscitation decisions, many do not discuss these preferences with healthcare professionals.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Survivors of acute NIV should therefore have future treatment plans discussed and documented, including advance-care planning and patient preferences regarding emergency care decisions in the likely event of future clinical deterioration. Despite international consensus regarding the importance of advance-care planning in patients with severe COPD, barriers to this process persist [31]. A qualitative study by Smith et al [32] demonstrated that although many survivors of acute NIV have contemplated their mortality and preferences regarding future treatment and resuscitation decisions, many do not discuss these preferences with healthcare professionals.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Patienten, Angehörige sowie Ärzte scheuen verständlicherweise das Thema. Allerdings bessert die „vorausschauende Behandlungsplanung“ die Lebensqualität der betroffenen Patienten und reduziert die Kosten am Ende des Lebens 10 . Gerade Patienten mit häuslicher Beatmung sind oft mit ihrer eingeschränkten Lebenssituation unzufrieden und einige von ihnen wären in Betrachtung dieser Situation lieber gestorben als so zu leben 11 .…”
Section: Diskussionunclassified
“…Bei der chronisch-obstruktiven Lungenerkrankung (COPD) werden u. a. Luftnot, Fatigue oder Kachexie als führende Symptome angegeben [7][8][9][10][11][12][13]. Art und Ausprägung der Symptome ähneln denen von Patienten mit fortgeschrittenem Bronchialkarzinom.…”
Section: Introductionunclassified